Splitting Leagues - Matthias Kräkel (University of Bonn, Bonn Graduate School of Economics (BGSE), 2003)
Splitting leagues or tournaments seems to be puzzling when agents are homogeneous and splitting leads to a negative competition effect. However, it can be shown that the principal can nevertheless benefit from splitting. First, splitting can be used as a divide-and-rule strategy by the principal to create additional incentives when collusion among the agents is possible. Second, splitting leagues gives the principal the opportunity to introduce promotions and relegations between nested tournaments (i.e., tournaments that are intertemporally linked), which also enhances incentives.
Keywords: M5; J4; J3; 330; collusion; leagues; promotion; relegation; tournaments; Agency Theory; Wettbewerb; Theorie; tournaments